2014
DOI: 10.5604/12321966.1129926
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of posture in children with very low lead exposure, and modification by VDR FokI genotype

Abstract: Effects on CNS, as reflected by disturbances of posture, were present at very low lead exposure (B-Pb<50 µg/L), and the effect was significantly greater at such low B-Pbs than at higher. VDR FokI significantly modified the effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
2
4
0
1
Order By: Relevance
“…The similar conclusion results from investigations of Rezende et al in pregnant women, in whom the haplotype combining the f, a, and b alleles for the FokI, ApaI and BsmI polymorphisms, respectively, was associated with significantly lower lead blood concentration (Rezende et al, 2010). The FokI polymorphism did not crucially affect the toxicological parameters and cognitive functions in children of urban Upper Silesian region, which was proved in the study of Pawlas et al Tendency for ff carriers to higher sway area was observed (Pawlas et al, 2012(Pawlas et al, , 2014.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The similar conclusion results from investigations of Rezende et al in pregnant women, in whom the haplotype combining the f, a, and b alleles for the FokI, ApaI and BsmI polymorphisms, respectively, was associated with significantly lower lead blood concentration (Rezende et al, 2010). The FokI polymorphism did not crucially affect the toxicological parameters and cognitive functions in children of urban Upper Silesian region, which was proved in the study of Pawlas et al Tendency for ff carriers to higher sway area was observed (Pawlas et al, 2012(Pawlas et al, , 2014.…”
Section: Discussionsupporting
confidence: 82%
“…The polymorphism of locus rs1139488 (RsaI) was the subject of research Pawlas et al, which show no significant differences in blood lead level of any genotypic form (Pawlas et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings illustrate that cadmium (Cd) and Pb exposures, including those from environmental and food sources, may be contributing to fractures, especially in older adults and those who smoke (Dahl et al, 2014; Engström et al, 2012; Staessen et al, 1999). Similar associations have been found between increased Pb exposure and impairments in postural sway or balance (Dick et al, 1999; Iwata, Yano, Karita, Dakeishi, & Murata, 2005; Pawlas, Broberg, Skerfving, & Pawlas, 2014).…”
Section: Resultssupporting
confidence: 73%
“…A prevalência do alelo variante deste SNP, em nosso estudo, foi compatível com a encontrada por outros autores no Brasil e no exterior (SANTOS et al, 2010;BATSCHAUER et al, 2011;LIAN et al, 2013;SZYMANSKA-CHABOWSKA et al, Pb-tíbia já foi associado à presença dos alelos polimórficos VDR rs1544410 (SCHWARTZ et al, 2000;WEAVER et al, 2005;PAWLAS et al, 2015) e VDR rs2228570 (PAWLAS et al, 2015). Contudo, estes mesmos polimorfismos já foram relacionados a menores concentrações sanguíneas de Pb (HAYNES et al, 2003;GARCÍA-LESTÓN et al, 2012), além de haver estudos onde nenhuma associação significativa foi observada, de forma semelhante ao relatado em nosso trabalho (PAWLAS et al, 2014;KAMEL et al, 2003).…”
Section: O Estresse Oxidativo é Um Dos Efeitos Tóxicos Mais Relevanteunclassified